Implementasi Pendekatan Saintifik Kurikulum 2013 pada Peserta Didik Kelas I Tema 5 Pengalamanku di SD Muhammadiyah 24 Surakarta Tahun Ajaran 2016/2017 - Sholikhah, Fitria Jamilatus; , Dra. Ratnasari Diah Utami, M.Si., M.Pd; , Drs. Mulyadi Sri Kamulyan, M.Pd (2017)
This study aimed to describe: 1) Preparation of the implementation of learning to approach scientific curriculum 2013 class 1 theme 5 in SD Muhammadiyah 24 Surakarta, 2) The approach of the scientific curriculum of 2013 grade I theme 5 in SD Muhammadiyah 24 Surakarta, 3) Evaluation approach scientific curriculum 2013 class I theme 5 in SD Muhammadiyah Surakarta 24, 4) Obstacles and solutions scientific approach to the curriculum in 2013 grade I theme 5 experiences in SD Muhammadiyah 24. this type of research is qualitative research. Data collection techniques used were interviews, observation, and documentation. Data analysis through the steps of data reduction, data presentation, and verification conclusion. The results showed that 1) Preparation of teaching practices that make prota, promissory notes, syllabi, lesson plans, and make instructional media, 2) Step-by-step approach is scientific is already implemented in the learning sequence, 3) evaluation of the approach scientifically conducted in accordance core competence, basic competence and indikato and using authentic assessment, 4) Barriers scientific approach include: delays in providing student books and teacher books. Making RPP teacher takes a lot; The scientific approach is difficult to emerge as observe, to question and analyze; evaluation of learning and assessment of learning takes time, effort, and understanding. Solutions applied include teachers looking for source references, learning materials in outline, and using the experience of learners); RPP made directly to some learning, providing stimulus, reinforcement and motivation to the peseta learners; Evaluation of learning after the end of the lesson, to understand making judgments reverensi teachers sought from various sources.